Environmental Health for All : Risk Assessment and Risk Communication for National Environmental Health Action Plans - Briggs, David J. (NATO science series. Environmental security, 1999)
The development of National Environmental Health Action Plans (NEHAPs) has become a major initiative in Europe, with 51 countries now committed to introducing plans by the new millennium. This book is the first substantive attempt to review recent experience in formulating these plans, and to examine and assess the technical and psycho-sociological tools available to support such plans. It brings together results from four of the leading countries involved in NEHAP developments (Sweden, Czech Republic, Romania and Poland) and describes the techniques that were used to identify and prioritise key environmental issues, and to identify policy responses. It also provides an up-to-date review of the methods and tools available for risk assessment, risk communication and priority setting, which are relevant not only to NEHAPs but to environmental planning more generally, and to many other areas of public policy. The discussion of these techniques is supported by numerous case studies, and is concluded by a series of chapters reflecting on the conceptual and research issues that still need to be addressed. The book will thus be of interest and value to all those concerned with developing and applying environmental health policy, to environmental epidemiologists, and to students and practitioners in the wider area of public policy.